142 A Community Mini-Grant Program: Community Leaders and Academic Partners Work Together to Improve Health in Appalachian Kentucky. (April 2022) - Hall, Ashley G.; Kern, Philip A.; Mudd-Martin,
Abstract : OBJECTIVES/GOALS: Through the Community Mini-Grant program, the University of Kentucky Center for Clinical and Translational Science Community Engagement and Research Core (CERC) provides a unique funding mechanism designed to empower community response by supporting local solutions to complex health issues facing central Appalachian Kentucky communities. METHODS/STUDY POPULATION: Four 2500 grants are awarded annually to Appalachian organizations to implement evidence-based programs responsive to community-identified priority health needs. The CERC also supports program implementation and evaluation by facilitating collaborations between the organizations, community practitioners, and academic researchers. RESULTS/ANTICIPATED RESULTS: Since inception, grants have been awarded to 20 community organizations in 14 Appalachian counties. Health issues addressed have ranged from Alzheimers disease, cancer treatment and prevention, obesity, healthy lifestyle, and chronic disease management and prevention. Evidence-based programs have focused on improving health outcomes among older adults, caregivers, youth, children, women and infants, and families. Program outcomes have included immediate health benefits and long-term benefits resulting from community adoption of and ongoing financial support for programs. As example, results of an evidence-based educational program to improve diabetic foot assessment among clinicians in a large Appalachian healthcare network resulted in establishment of a traveling podiatrist program. DISCUSSION/SIGNIFICANCE: Community mini-grant recipients have successfully implemented projects that address the most significant health disparities in the region. Also of benefit are expanded partnerships that are foundational to the creation of new academic-community collaborations to address the challenging health issues of Appalachian populations in Kentucky.